A U-shaped curve phenomenon of international language on output growth: empirical evidence. Issue 8 (3rd May 2020) - Chen, Ku-Hsieh; Chen, To-Yu; Lin, Hsin-Hui
ABSTRACT: The contribution of international language proficiency on output growth for an economy is generally considered to be monotonously positive, at least irrelevant or non-negative. Nonetheless, the inference seems suspicious if one ponders over this from an aggregate aspect. This study hypothesizes a U-shaped curve for the proposition and conducts an empirical analysis with 40 non-English-speaking countries based on the English Proficiency Index (EPI) from 2011 to 2016, developed by Education First. The outcome reveals that along with an increase in EPI, the effect on growth is shown initially to be negative and then turns positive. Accordingly, while plotting the relationship between the two variables on a two-dimensional graph, a U-shaped curve appears, and the lowest turning point is located at 57.42 of the EPI. It is further manifested that during the sample period, about 36% of the observations yielded a positive effect, but the others were non-positive. Finally, the empirical analysis also shows that two-way feedback causality exists between the international language proficiency and output growth.